Effect of nitrogen and application ways of a plant biostimulant on different wheat genotypes contrasting in stature - Almeida, Adriana Queiroz de [UNESP]; Hedden, Peter; Soratto, Rogério Peres [UNESP] (Academic Journals, 2014)
Wheat (Triticum aestivum L.) is the leading crops for human nutrition in Europe and in most temperate regions worldwide. This crop is demanding in nutrients, among them nitrogen (N) is absorbed in higher amounts and its efficiency of utilization can be increased with a plant biostimulant use. The objective of this work was to evaluate the influence of different N levels and ways of biostimulant application on genotypes growth of wheat, tall and semi dwarf. The experiment was carried out, in 2010, at greenhouse located in Rothamsted Research Institute, Harpenden – United Kingdom. The design was in randomized blocks, with four replications. The experiment was a 3x2x2 factorial arrangement consisting by three ways of application using a commercial biostimulant and two N levels provided by nutritive solution and two spring wheat genotypes (Green – tall and Red – semi dwarf). Isolated effect of biostimulant use was not observed on fresh matter and dry matter of aboveground part and root; however, N levels affected same variables, except root dry matter. A significant interaction between biostimulant and N was observed on dry matter of aboveground part. No significant results were found for length, surface, diameter and volume of root after biostimulant application and different N levels in Green and Red genotypes. Seed treatment and leaf spray with biostimulant did not promoted effects on N and C content in aboveground part and root for tall or dwarf wheat; on the other hand, significant differences were observed when N was applied through nutritive solution. Biostimulant application did not promoted increase on growth, N and C content of aboveground part, metabolites production and components of wheat production. Use of N promoted increase on fresh and dry matter of wheat, except dry matter of root, moreover, additions were observed in its content in aboveground part of wheat.
Keywords: Semi dwarf; Nutrients; Plant regulator; Root growth; Content; Triticum aestivum; Nutrição de plantas; Regulador vegetal; Crescimento radicular